SIMS measurement of magnesium isotopic ratios in chondrites - Nishimura, Hiroshi; Okana, Jun (1981)
P(論文) Isotopic ratios of ^<25>(Mg)/^<24>(Mg) and ^<26>(Mg)/^<24>(Mg) have been measured for Mg-rich and Al-poor portions of Yamato, Plainview, Bruderheim, Leedey, Potter, Murchison, Leoville, Allende and Bondoc Peninsula meteorites with a Hitachi IMA 2A ion microprobe mass analyzer. Terrestrial samples of forsterite, biotite and anorthite have been also analyzed. In the three isotope plot, the data for ordinary chondrites of petrological types 5 and 6,an achondrite, a stony-iron meteorite and terrestrial samples are along the normal mass fractionation line through the reference point. On the contrary, the data for ordinary chondrites of petrological type 4 and carbonaceous chondrites fall on a straight line with the slope of unity with a few exceptions. This line can be explained to be the mixing of original magnesium and practically pure ^<24>(Mg). This can be an evidence for the two component hypothesis of the primordial solar nebula. departmental bulletin paper